Educating children of immigrants: Closing the gap in Norwegian schools - Bernt Bratsberg; Oddbjørn Raaum; Knut Røed (Institute for the Study of Labor (IZA), 2011)
Children of immigrant parents constitute a growing share of school cohorts in many OECD countries, and their educational performance is vital for successful social and economic integration. This paper examines educational outcomes of first and second generation non- OECD immigrants in Norway. We show that children of immigrants, and particularly those born outside Norway, are much more likely to leave school early than native children. Importantly, this gap shrunk sharply over the past two decades and second generation immigrants are now rapidly catching up with the educational performance of natives. For childhood immigrants, upper secondary completion rates decline with age at arrival, with a particularly steep gradient after age seven. Finally, we find that immigrant-native attainment gaps disappear when we condition on grade points from compulsory school.
urn:nbn:de:101:1-201112136915
Keywords: J15; I21; I24; 330; immigrant children; educational attainment; school performance; Kinder; Migranten; Bildungsniveau; Bevölkerung; Norwegen